Transition from early childhood education to primary school : what works - Yeboah, David Achanfuo (2001)
Examines the literature on transition to school, and discusses the importance of the transition and the need to minimise its possibly adverse effects. Identifies and discusses the various factors which facilitiate and enhance successful transition from early childhood education to primary school.